Cognitive and discursive features of Joe Biden's address to the joint session of the United States Congress on April 29, 2021 - O.I. Afonina (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article examines the cognitive and discursive aspects of Joe Biden’s April 2021 statement on the epidemiological situation in the United States and the American Jobs Plan. The relevance of the research stems from the need to better understand the tactics and strategies employed by politicians to influence their audiences at the times when politics plays a key role in our lives. Here, the lexical and syntactic features of U.S. President Joe Biden’s speech were considered in order to describe him as a linguistic personality. The main methods used were descriptive, contextual, and keyword analyses. A number of examples prove that Joe Biden uses very expressive linguistic devices to achieve the maximum effect on his listeners: firstly, the U.S. President was found to place particular emphasis on stylistic devices; secondly, various parenthetical elements were highlighted; thirdly, certain distinctive expressive devices were identified; finally, special attention was given to the study of the syntax of the statement. Based on the obtained results, the linguistic personality of Joe Biden within political discourse was characterized in detail. For example, he uses linguistic and pragmatic devices to influence the audience rather than to convey the message. An important generalization is that the discourse of a politician reflects social problems, and the functions of lexical means vary depending on the socio-political situation in a state.